Self-assembly of a Si-based cage by the formation of 24 equivalent covalent bonds. Issue 84 (4th October 2018) - Holmes, Jessica L.; Abrahams, Brendan F.; Ahveninen, Anna; Boughton, Berin A.; Hudson, Timothy A.; Robson, Richard; Thinagaran, Dinaiz
Abstract : A covalent, robust, nano-sized tetrahedral cage containing six silicon centres has been synthesised and structurally characterised. Abstract : A robust, nano-sized covalent cage, of composition, [(PhSi)6 (ctc)4 ] 6− (H6 ctc = cyclotricatechylene) has been prepared in a simple reaction in good yield. The tetrahedral anionic cage is stable in both the solid and solution state and exhibits an affinity for Cs + ions which bind to the internal surface of the cage.